1997
DOI: 10.1111/j.1432-1033.1997.t01-1-00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Drosophila Proximal‐Sequence‐Element‐Binding Protein Involved in Transcription of Small Nuclear RNA Genes

Abstract: In a wide variety of eukaryotic organisms, transcription of small nuclear RNA (snRNA) genes is dependent upon a proximal sequence element (PSE) located upstream of position -40 relative to the transcription start site. There is little or no existent knowledge concerning the PSE-binding proteins of organisms other than human. Here, we report the purification of a fraction enriched in the Drosophila melanogaster PSE-binding protein (DmPBP). DmPBP forms a highly specific complex with the PSE. The protein stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
40
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 30 publications
5
40
0
Order By: Relevance
“…Because each of these subunits is required for snRNA transcription by either RNAP II or RNAP III, it seems that the same protein complex functions at both classes of vertebrate snRNA gene promoters. The fact that the PSEA plays a major role in determining RNA polymerase specificity in Drosophila poses the question of whether a similar complex functions at both RNAP II and RNAP III snRNA promoters in insects.Our lab recently reported the partial purification and characterization of the D. melanogaster PSEA-binding protein (DmPBP) (27). Like SNAP c /PTF, DmPBP is a multisubunit…”
mentioning
confidence: 99%
“…Because each of these subunits is required for snRNA transcription by either RNAP II or RNAP III, it seems that the same protein complex functions at both classes of vertebrate snRNA gene promoters. The fact that the PSEA plays a major role in determining RNA polymerase specificity in Drosophila poses the question of whether a similar complex functions at both RNAP II and RNAP III snRNA promoters in insects.Our lab recently reported the partial purification and characterization of the D. melanogaster PSEA-binding protein (DmPBP) (27). Like SNAP c /PTF, DmPBP is a multisubunit…”
mentioning
confidence: 99%
“…Previous work had shown that D. melanogaster U1 and U6 snRNA genes can be faithfully transcribed in vitro by using unfractionated SNF prepared from 0 -12-h fruit fly embryos (22)(23)(24)(25). As a control for TRF1-dependent transcription, we also employed a tRNA Arg -maxi gene template (20).…”
Section: Resultsmentioning
confidence: 99%
“…As controls, three U1 snRNA gene loci and three tRNA gene loci were also analyzed. Furthermore, because DmSNAPc is required for transcription of both U1 and U6 snRNA genes (23) but not for the transcription of tRNA genes, we also examined DmSNAPc occupancy by using antibodies against DmSNAP43.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations